Історична компаративістика досліджень імперій і цивілізацій: теоретичні підходи й концепції - Мартинов, А. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2019)
Історичний процес глобалізації актуалізував наукову проблему зіткнення або діалогу локальних цивілізацій. Дискусійним залишається питання співвідношення понять імперія й локальна цивілізація. Упродовж
тривалого хронологічного періоду від модерну до постмодерну проявили
себе імперські утворення різного типу. В минуле пішли традиційні імперії, які існували на основі застарілих економічних укладів. Нез’ясованим у історичній літературі залишається питання діалектики зв’язків між
процесом глобалізації та імперським порядком. На цьому тлі ключовою
проблемою стає продовження існування імперських структур у віртуальному просторі. На думку багатьох дослідників цивілізаційне розуміння
історії має унеможливити спроби абсолютизувати вузькі визначення
поняття цивілізації, за якими приховуються прагнення видати певну
макроконцепцію за єдино правильну теорію цивілізаційного розвитку. Водночас розвиток діалогу між прихильниками різних підходів до вивчення проблем історії цивілізацій, який уже понад століття розгортається в історіографії, дає можливість наблизитися до більш адекватного розуміння різних аспектів цивілізаційної теорії і теорії імперського розвитку. The article analyses the system of international relations in the context of
transformation of a unipolar world order, led by the United States, into a
multipolar system. The globalization process actualized the problem of dialogue
among cultures and civilizations as well as clash of civilizations. Questions
of the correlation between the concepts of empire and local civilization remain
somewhat debatable. Diverse types of empires have emerged as important
political players over a prolonged period of time from modern to postmodern.
Traditional empires with their economic, spiritual and cultural environment
became history. The question remains about the relationship between globalization
and intellectual imperialism. This recognised that the key issue is the
introduction of information technologies and the globalization in cyberspace.
Theories of globalization claim to be able to explain all the major changes
occurring in today’s world. Hence, there are a host of competing interpretations
of the new global society, due to which the idea of globalization has
remained vague and failed to go beyond the general concepts of global imperia
or global civilization. The materialist conception of history regards material
production and people’s transforming activity as the basis of history, thereby
shedding light on the objective laws of the development of human society,
along with the sources and driving forces behind the history of the world.
Globalization is defined as the integration of productive forces of humanity on
a global scale, which constitutes the material basis for its worldwide unity, the
unity of its history and societal development. Such consolidation becomes
possible only after and due to the global expansion of modern capitalism.